Morphology of Models Manufactured by SLM Technology and the Ti6Al4V Titanium Alloy Designed for Medical Applications - Damian Gogolewski (MDPI AG, 2021)
This paper presents the results of an experimental study to evaluate the possibility of using SLM additive technology to produce structures with specific surface morphological features. Qualitative and quantitative tests were conducted on samples fabricated by 3D printing from titanium (Ti6Al4V)-powder-based material and analysed in direct relation to the possibility of their use in medicine for the construction of femoral stem and models with a specific degree of porosity predicted by process-control in the self-decision-making 3D printing machine. This paper presents the results of the study, limitations of the method, recommendations that should be used in the design of finished products, and design proposals to support the fabrication process of 3D printers. Furthermore, the study contains an evaluation of how the printing direction affects the formation of certain structures on the printed surface. The research can be used in the development of 3D printing standardization, particularly in the consideration of process control and surface control.